2010
DOI: 10.1002/rcm.4831
|View full text |Cite
|
Sign up to set email alerts
|

Surface swabbing technique for the rapid screening for pesticides using ambient pressure desorption ionization with high‐resolution mass spectrometry

Abstract: A rapid screening method for pesticides has been developed to promote more efficient processing of produce entering the United States. Foam swabs were used to recover a multiclass mixture of 132 pesticides from the surfaces of grapes, apples, and oranges. The swabs were analyzed using direct analysis in real time (DART) ionization coupled with a high-resolution Exactive Orbitrap™ mass spectrometer. By using a DART helium temperature gradient from 100-350°C over 3 min, a minimal separation of analytes based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 15 publications
1
67
0
Order By: Relevance
“…The wire screen was positioned in the DART TM, which has 10 holes designed to orient the screen such that the heated He carrier gas passes directly through the center of each hole [30]. Individual 10 μL aliquots of each of the six working solutions were pipetted onto the center region of each wire screen.…”
Section: Operational Methodsmentioning
confidence: 99%
“…The wire screen was positioned in the DART TM, which has 10 holes designed to orient the screen such that the heated He carrier gas passes directly through the center of each hole [30]. Individual 10 μL aliquots of each of the six working solutions were pipetted onto the center region of each wire screen.…”
Section: Operational Methodsmentioning
confidence: 99%
“…If no specimen pretreatment is carried out to the surface, it might result in poor sensitivity. Thus, effective contaminant detection was possible by applying swabbing methods on the surfaces of fruits and vegetables [104,105]. Thus, by spiking different pieces of fruits with a complex mixture of pesticides, it was demonstrated that swabs increased sample throughput by reducing sample preparation and analysis time [104].…”
Section: Dart-hrmsmentioning
confidence: 99%
“…e thermally desorbed analytes are subsequently carried by a nitrogen stream into an electrospray plume and ionized via ion-molecule reactions with the charged solvent species to form analyte ions. Even though sampling, desorption, ionization, and detection are separate events, a typical TD-ESI/ MS analysis takes less than 30 s. Compared to other ambient ionization sources such as desorption electrospray ionization (DESI), [9][10][11] direct analysis in real time (DART), 12,13) and electrospray-assisted laser desorption ionization (ELDI), 14) where samples must meet the ion source, the use of a direct sampling probe in TD-ESI/MS makes the technique suitable to analyze pesticides and drugs on oversized or immovable objects and in viscous biological solutions. 7,8,15,16) During early rescue, gastric lavage is a common practice for removing sustained-release medications and ingested substances.…”
Section: Introductionmentioning
confidence: 99%